2023
DOI: 10.3390/nu15040995
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Dependent Allergy in Patients with Celiac Disease: A Systematic Review

Abstract: In order to answer the question if an IgE-mediated allergy (A-IgE) may occur in subjects with celiac disease (CD), a systematic review was performed of available publications collected in the United States National Institute for Biotechnology Information/National Institutes of Health/National Library of Medicine/PubMed database up to 28 December 2022, with the use of the following keywords “allergy&celiac/coeliac”, “sensitization&celiac/coeliac”, and “anaphylaxis&celiac/coeliac” compared in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Our study, utilizing TSMR, offers new insights into the genetic causality between celiac disease and type 2 inflammatory diseases, moving beyond the observational correlations highlighted in prior research (5,11,12,(18)(19)(20)(21)24). Specifically, our findings reinforce the epidemiological evidence for shared genetic pathways in the inflammatory processes of celiac disease and type 2 inflammatory diseases (2,9,12).…”
Section: Interpretation Of Main Results and Their Implicationssupporting
confidence: 73%
See 1 more Smart Citation
“…Our study, utilizing TSMR, offers new insights into the genetic causality between celiac disease and type 2 inflammatory diseases, moving beyond the observational correlations highlighted in prior research (5,11,12,(18)(19)(20)(21)24). Specifically, our findings reinforce the epidemiological evidence for shared genetic pathways in the inflammatory processes of celiac disease and type 2 inflammatory diseases (2,9,12).…”
Section: Interpretation Of Main Results and Their Implicationssupporting
confidence: 73%
“…Similarly, Majasiak et al’s systematic review, the first of its kind, underscored the possibility of concurrent allergic IgE-mediated allergy (A-IgE) and CD. This review highlighted cases where CD patients exhibited A-IgE to allergens, particularly wheat, leading to symptoms like atopic dermatitis and anaphylactic shock, even after adopting a gluten-free diet (19). These epidemiological insights, mainly the association of celiac disease with autoimmune disorders and allergies (20,21), reinforce the significance of our genetic analysis, suggesting that the observed genetic links may reflect a broader, clinically relevant interaction between CD and type 2 inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The extra-gastrointestinal symptoms may include chronic fatigue, headaches, anemia, and elevated liver enzyme levels. Although CD has long been known to co-occur with autoimmune conditions (such as type 1 diabetes mellitus, autoimmune thyroid, or liver diseases) or genetic syndromes (such as Down syndrome, Turner syndrome, and Williams syndrome) [2], there have been few studies on the co-existence of CD and immunoglobulin E (IgE)-mediated allergies [3]. In CD, the sole factor that induces autoimmunity are immunoreactive gluten peptides, whereas in allergies, the causative factors may be either inhalant or food allergens and other (whose route of exposure is other than via inhalation or ingestion, for instance, via insect stings or via direct dermal contact).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the seemingly mutually exclusive pathogeneses of CD and IgE-mediated allergy, there have been studies indicating the co-existence of both conditions. A systematic review of studies by our research group [3] revealed a handful of original articles [8][9][10][11] in which authors reported that patients with CD may develop an allergy that manifests in a similar way to that in non-CD subjects, i.e., with atopic dermatitis, vomiting, urticaria, angioedema, anaphylactic shock, etc. In those studies, patients with CD were most often allergic to wheat, which may be due to the fact that this allergen was the one most frequently studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the gluten-free diet (GFD) may not always be effective [7], classically either due to insufficient adherence to the diet [8] or to crosscontamination of naturally gluten-free foods and products labeled gluten-free [6]. Interestingly, some authors have suggested that the persistence of gastrointestinal symptoms may be due to the coexistence of other disorders, which must therefore be considered [8][9][10][11]. Furthermore, it has been hypothesized that abnormal intestinal permeability in patients with CD may enhance the passage of antigenic food proteins through the intestinal wall, thus predisposing the mucosal immune system to allergic reactions [8].…”
Section: Introductionmentioning
confidence: 99%